CRISPR/Cas9 in Stem Cell Research: Current Application and Future Perspective - Patmanathan, Sathya N.; Gnanasegaran, Nareshwaran; Lim, Moon Nian; Husaini, Roslina; Fakiruddin, Kamal Shaik; Zakaria, Zubaidah (Current Stem Cell Research & Therapy, 2018)
The clustered regularly interspaced short palindromic repeats-associated protein 9 or CRISPR/Cas9 system is one of the hottest topics discussed lately due to its robustness and effectiveness in genome editing. The technology has been widely used in life science research including microbial, plant, animal, and human cell studies. Combined with the pluripotency of stem cells, the technology represents a powerful tool to generate various cell types for disease modeling, drug screening, toxicology, and targeted therapies. Generally, the CRISPR/Cas9 system has been applied in genetic modification of pluripotent or multipotent stem cells, after which the cells are differentiated into specific cell types and used for functional analysis or even clinical transplantation. Recent advancement in CRISPR/Cas9 technology has widened the scope of stem cell research and its therapeutic application. This review provides an overview of the current application and the prospect of CRISPR/Cas9 technology, particularly in stem cell research and therapy.
Keywords: CRISPR/Cas9